Single phase ac regulator power electronic trainer / Jackari Mohammad Alias@Awang - Mohammad Alias@Awang, Jackari (2005)
This report illustrates the design and development of variable pulse generator and AC regulator circuit that is suitable for the single phase regulator experiment used in power electronic laboratory. Two mode of AC regulator will be used they are singlephase half-wave AC regulator and single-phase full-wave AC regulator. The design is based on Programmable Interface Controller (PIC) as the main processing unit. For triggering firing angle (a) of the thyristor a variable analog input is used to vary from 0° to 180° and interface with the Programmable Interface Controller (PIC) to produce variable pulse angle. The observation can be made through the waveform produced by the rectifier circuit where it is represent by mean voltage.